Evaluation of Parameters Affecting Magnetic Abrasive Finishing on Concave Freeform Surface of Al Alloy via RSM Method. (29th August 2016) - Vahdati, Mehrdad; Rasouli, SeyedAlireza
Abstract : The attempts of researchers in industries to obtain accurate and high quality surfaces led to the invention of new methods of finishing. Magnetic abrasive finishing (MAF) is a relatively new type of finishing in which the magnetic field is used to control the abrasive tools. Applications such as the surface of molds are ones of the parts which require very high surface smoothness. Usually this type of parts has freeform surface. In this study, the effect of magnetic abrasive process parameters on freeform surfaces of parts made of aluminum is examined. This method is obtained through combination of magnetic abrasive process and Control Numerical Computer (CNC). The use of simple hemisphere for installation on the flat area of the magnets as well as magnets' spark in curve form is a measure done during testing the experiments. The design of experiments is based on response surface methodology. The gap, the rotational speed of the spindle, and the feed rate are found influential and regression equations governing the process are also determined. The impact of intensity of the magnetic field is obtained using the finite element software of Maxwell. Results show that in concave areas of the surface, generally speaking, the surface roughness decreases to 0.2 μ m from its initial 1.3 μ m roughness. However, in some points the lowest surface roughness of 0.08 μ m was measured.